2021
DOI: 10.1101/2021.02.14.431174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct activation of endothelial cells by SARS-CoV-2 nucleocapsid protein is blocked by Simvastatin

Abstract: Emerging evidence suggests that endothelial activation plays a central role in the pathogenesis of acute respiratory distress syndrome (ARDS) and multi-organ failure in patients with COVID-19. However, the molecular mechanisms underlying endothelial activation in COVID-19 patients remain unclear. In this study, the SARS-CoV-2 viral proteins that potently activate human endothelial cells were screened to elucidate the molecular mechanisms involved with endothelial activation. It was found that nucleocapsid prot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…1 E). Qian et al reported that the nucleocapsid (N) protein of SARS-CoV-2 was able to trigger endothelial inflammation by activating NFκB and MAPK signal pathway via TLR2 [ 67 ]. Altogether, these evidences have demonstrated the possibility of host cell entry or activation through expression of EC surface receptors; however, more work is needed to validate these findings in vivo .…”
Section: Evidence Of Direct Infection Of Ecs By Sars-cov-2mentioning
confidence: 99%
“…1 E). Qian et al reported that the nucleocapsid (N) protein of SARS-CoV-2 was able to trigger endothelial inflammation by activating NFκB and MAPK signal pathway via TLR2 [ 67 ]. Altogether, these evidences have demonstrated the possibility of host cell entry or activation through expression of EC surface receptors; however, more work is needed to validate these findings in vivo .…”
Section: Evidence Of Direct Infection Of Ecs By Sars-cov-2mentioning
confidence: 99%
“…A significant body of evidence indicates endothelial activation and pro-inflammatory cytokines play a critical role in the pathogenesis of the SARS-CoV-2 infection [19]. Additionally, a potential caveat to using HbA as a countermeasure for COVID-19-induced hypoxia is that hemoglobin has been reported to cause stimulation of IL-6, IL-8, and tumor necrosis factor-α from leukocytes in whole blood [20].…”
Section: S1 Protein Triggered Endothelial Activation and Induced A Pro-inflammatory Response In Hpaecmentioning
confidence: 99%
“…The ultrastructural morphology of coronavirus particles we obtained by TEM examination of the tissue of the lungs and lymph nodes is similar to the data reported by other researchers, both in native tissues and in cell cultures [ 43 , 44 , 45 ]. The detection of SARS-CoV-2 virions in the cytoplasm of endothelial cells and its possible impact on the development of systemic pathology have been previously described by other authors [ 46 , 47 , 48 , 49 ]. The mechanism of lymphopenia due to the direct viral infection of T-lymphocytes and subsequent massive apoptosis has been described as related to the SARS-COV-2 coronaviruses MERS-CoV and SARS-CoV [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 75%